Creative Industry Product Innovation: Are Scamper Techniques Effective? - Arianto, Antoni Setyo; Soeprijatno, Edy Djoko (Proceeding Kilisuci International Conference on Economic & Business, 2025)
The purpose of the study is to : analyze the application of the Scampermethod in improving product innovation in Lucius ArtDesign/Method/Approach: The method used in this study is aqualitative approach. Through a case study approach, data wascollected through interviews with artisans, and observationsResearch Findings: Lucius Art has a big challenge in creating a productthat can compete in the global market. One way to overcome thisproblem is to encourage product innovation through a systematicapproach such as the Scamper technique.Theoretical contribution/originality: this study enriches the literatureon the application of the Scamper method in the context of the arts andcrafts industry, as well as providing new insights related to productinnovation in small and medium enterprises (SMEs).Practitioner/Policy Implications: This research can be used as areference for creative industry players who want to develop productinnovations systematically.Research limitations: This research focuses on one business venture,Lucius Art, the results of which may not be generalized to the arts andcrafts industry as a whole